Presentation of cysticercosis of the lateral pterygoid muscle as temporomandibular disorder: A diagnostic and therapeutic challenge - Mythili Kalladka; Anuradha Navaneetham; Eli Eliav; Junad Khan; Gary Heir; Mel Mupparapu (Wolters Kluwer Medknow Publications, 2018)
Orofacial pain can often be the chief complaint of many systemic disorders. Cysticercosis involving the lateral pterygoids may cause limitation of mouth opening and may mimic clinical symptoms of a temporomandibular disorder. A 37-year-old female presented with 1-month-old complaint of limited mandibular range of motion. She reported a similar episode a year earlier and was diagnosed with a temporomandibular joint disorder by her primary dentist. Comprehensive intra- and extra-oral examinations were performed, which revealed a limitation of mouth opening accompanied by mild limitation of contralateral excursion. A magnetic resonance imaging revealed a ring-enhancing lesion within the left pterygoid muscle suggestive of cysticercosis. The patient was referred to her primary care physician for further treatment and given physical therapy (stretching exercises) to improve mouth opening. One week later, she developed lesions in the arm and trunk. Further ultrasound imaging of the abdomen and the forearms confirmed the diagnosis of cysticercosis. She was treated with albendazole, physiotherapy, joint stabilization appliance, and had eventual complete recovery. This case emphasizes the importance of diagnosis of a systemic condition that may have serious implications, if untreated, and the importance of a comprehensive evaluation, workup, and multidisciplinary management.